Urban Living Lab for Local Regeneration Beyond Participation in Large-scale Social Housing Estates - Aernouts, Nele; Cognetti, Francesca; Maranghi, Elena (The Urban Book Series, 2023)
This open access book provides an integrated overview of the challenges and resources of large-scale social housing estates in Europe and outlines possible interdisciplinary approaches and tools to promote their regeneration. It especially focuses on the tool of urban living labs, as promising in promoting new and more effective local governance and in including the different actors into the planning process. The book combines theory and practice, since it is the result of action-research conducted in different social housing estates all over Europe. Building on the results of the SoHoLab project (2017-2020), the book benefits from a multidisciplinary perspective, since the researchers involved belong to the fields of anthropology, urban planning, architecture, urban sociology. The project combined theoretical reflections with the installation and/or the consolidation of Urban Living Labs, run by universities, in large social housing estates in three European cities: Brussels, Milan and Paris.